(3EecGfjI GSJgOGa GdJVNe cEWGQ YGe ddSjGSI GdfbOjI ai Gdjef ai Xd HQfGeL GdEUdGM GdGbJUGOi(B1995-2010 / s - (3YGjV YbGd eMeO gLdGf s; (3MSf CMeO YHjO (B: s ((3GdbGgQI (B: s (3YGjV YbGd eMeO gLdGf (B: s, 2013)
(3gOaJ GdOQGSI Edi HMK EecGfjI GfJgGL SjGSI ESJgOGa GdJVNe cEWGQ ddSjGSI GdfbOjI ai Gdjef h Pdc ef NdGd JMdjd eDTQGJ JWHjb SjGSI ESJgOGa GdJVNe ai Gdjef hGJVM Gf hVY GdGbJUGO Gdjefi jSeM HJWHjb SjGSI GSJgOGa GdJVNe cEWGQ YGe ddSjGSI GdfbOjI eY VQhQI GdYed Ydi GSJeQGQ GdEUdGMGJ Ydi eSJhi GdGbJUGO Gdcdi h RjGOI ESJbdGdjI GdHfc GdeQcRi Gdjefi h VQhQI JWhjQ GdbWGY GdeGdi h RjGOI caGAI hMOGJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEbJUGO h GdYdhe GdSjGSjI (B- (3bSe GdEbJUGOs
(3UOQ GjVG cbQU eOeLs
Keywords: (3ESJgOGa GdJVNes; (3GdJVNe s; (3GdSjGSI GdfbOjI s